2013
DOI: 10.1186/2049-9256-1-7
|View full text |Cite
|
Sign up to set email alerts
|

Circadian and behavioural responses to shift work-like schedules of light/dark in the mouse

Abstract: BackgroundDisruption of circadian rhythms is associated with several deleterious health consequences and cognitive impairment. It is estimated that as many as one in five workers are exposed to this risk factor due to experiencing some degree of chronodisruption by way of recurring patterns of shift work. It is not presently clear therefore how efficiently the mammalian circadian system entrains to alternative light/dark cycles such as those found in shift work schedules.MethodsThe present study examines male … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 43 publications
1
24
1
2
Order By: Relevance
“…We next sought to examine the effects of miR-132 dysregulation on time-of-day dependent measures of learning and memory. To this end, we utilized the novel object location (NOL) task-a hippocampal-dependent memory test (Barker and Warburton 2011;Chao et al 2016) with an efficiency that has previously been shown to be influenced by circadian time (McGowan and Coogan 2013;Takahashi et al 2013. The NOL task examines the ability of a mouse to remember the location of an object after moving one of the two objects in the arena.…”
Section: Mir-132 Knockout and Mir-132 Transgenic Micementioning
confidence: 99%
“…We next sought to examine the effects of miR-132 dysregulation on time-of-day dependent measures of learning and memory. To this end, we utilized the novel object location (NOL) task-a hippocampal-dependent memory test (Barker and Warburton 2011;Chao et al 2016) with an efficiency that has previously been shown to be influenced by circadian time (McGowan and Coogan 2013;Takahashi et al 2013. The NOL task examines the ability of a mouse to remember the location of an object after moving one of the two objects in the arena.…”
Section: Mir-132 Knockout and Mir-132 Transgenic Micementioning
confidence: 99%
“…Rodent models of human shiftwork typically assess consequences of circadian disruption similar to that observed in human shiftwork, applying a variety of approaches including forced work during the normal rest phase (e.g., [31]), chronic jetlag (e.g., [32]), and non-entraining T-cycles (e.g., [33]). Few studies compare alternate schedules to minimize circadian disruption [34], and we are aware of no study testing different strategies to achieve a common simulated work schedule in animal models. For Study 2/DuPont and 3/Continental, we therefore developed a strategy where we aimed to evaluate and compare light-dark scheduling practices designed to avoid misalignment.…”
Section: Building Rodent Shiftwork Modelsmentioning
confidence: 99%
“…56 Interestingly some animal sleep restriction or shift work studies yield contradictory results and increased weight gain was not always observed in the challenged animals. 57,58 An important factor appears to be whether the sleep/shift paradigm also triggers mistimed food intake. 56,59 Food is a strong timing signal for peripheral tissue clocks.…”
Section: Peripher Al and Centr Al Interpl Ay In Homeos Tati C And Cmentioning
confidence: 99%